Application of the Qira'ah Mubah Method in Content on the Mubadalah.Id Website (In April 2023) - Iza Ma’rifah; Tantan Hermansah (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2024)
This research examines the relevance of Qira'ah Mubadalah's values and Kartini's thoughts in the content presented by Mubadalah.id during April 2023. The focus of the research is to understand the extent to which understanding and appreciation of Kartini's struggle is reflected in the content, as well as the influence and relevance of kartinian values in discussions and articles published on the platform. This relevance can be related to the values and perspective of Qira'ah Mub is one that has 3 indicators, namely a perspective (minzhar) that humanizes humans. Second, how to read (qira'ah) reference texts by placing men and women as subjects and complete humans. Third, the way of grouping or in Arabic terms (qa'idah) experiences, distractions, or cooperation between men and women is reflected in the word cloud and word frequency tables. This research is a type of qualitative research using text data in the media, samples and techniques for sampling news/documents (text) in the form of content on the Mubadalah.id website totaling 20 articles in the April 2023 time period. Data Sources and Data Collection Methods used are primary data collected from the website. Data is retrieved by downloading articles and saving them using pdf. And in data processing, data is processed using Nvivo software by utilizing the word cloud feature. The research results show that the content of Mubadalah.id predominantly discusses the issues of women, Kartini, figures, migrant workers, and the like. The word "woman" appeared 216 times, indicating the significance of the issue of women in the content.  Therefore, this research provides insight into the potential of preaching gender equality through social media and confirms the relevance of Kartini's values in a contemporary context.